2004
DOI: 10.1111/j.1365-2958.2004.04030.x
|View full text |Cite
|
Sign up to set email alerts
|

Fur functions as an activator and as a repressor of putative virulence genes in Neisseria meningitidis

Abstract: SummaryFur is a well-known iron-responsive repressor of gene transcription, which is used by many bacteria to respond to the low-iron environment that pathogens encounter during infection. Four promoters of Neisseria meningitidis predicted to have Fur-binding boxes were selected to study the molecular interactions between Fur and the promoter regions of genes expected to play a central role in survival and pathogenesis. We demonstrate that Fur acts not only as a repressor, but also as an activator of gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
156
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(166 citation statements)
references
References 44 publications
6
156
2
2
Order By: Relevance
“…The involvement of Fur in nitrogen metabolism has been reported in other bacteria. The Fur protein in Neisseria meningitidis activates the pan1 and norB genes, which encode nitrite and NO reductases, respectively (Delany et al, 2004), and the E. coli fur mutant exhibits a severe growth delay under aerobic conditions in the presence of nitrosylated glutathione or acidified nitrite (Mukhopadhyay et al, 2004). In contrast, we showed in this study that the fur mutation in strain ATCC 17616 causes hypersensitivity to nitrite under microaerobic conditions and also acidified nitrite (an NO producer) under aerobic conditions.…”
Section: Discussioncontrasting
confidence: 44%
“…The involvement of Fur in nitrogen metabolism has been reported in other bacteria. The Fur protein in Neisseria meningitidis activates the pan1 and norB genes, which encode nitrite and NO reductases, respectively (Delany et al, 2004), and the E. coli fur mutant exhibits a severe growth delay under aerobic conditions in the presence of nitrosylated glutathione or acidified nitrite (Mukhopadhyay et al, 2004). In contrast, we showed in this study that the fur mutation in strain ATCC 17616 causes hypersensitivity to nitrite under microaerobic conditions and also acidified nitrite (an NO producer) under aerobic conditions.…”
Section: Discussioncontrasting
confidence: 44%
“…There have been several reports that norB is activated by Fur aerobically (Sebastian et al, 2002;Grifantini et al, 2003Grifantini et al, , 2004; however, most of the data that support a role for Fur in activation of norB are based on demonstrating that Fur can bind to the site. In an in vitro transcription assay, Delany et al (2004) provide evidence that Fur may directly activate the meningococcal norB promoter, although our in vivo translational fusion analysis of the gonococcal norB upstream region shows no direct Fur activation (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Elimination of the Fur binding site in RUG7512 suggested that Fur had no role in the regulation of norB, despite several reports to the contrary in N. gonorrhoeae (Sebastian et al, 2002) and N. meningitidis (Grifantini et al, 2003(Grifantini et al, , 2004Delany et al, 2004). We therefore investigated the expression of norB : : lacZ fusions in a Dfur mutant (Fig.…”
Section: Indirect Regulation Of Norb By Furmentioning
confidence: 99%
“…IHF is a histone-like protein involved in the condensation of the bacterial chromosomal DNA that has been shown to act as a transcriptional regulator (14,15). Fur has been shown to mediate transcriptional regulation of numerous bacterial virulence factors in response to iron (16)(17)(18).…”
Section: Resultsmentioning
confidence: 99%
“…The histone-like protein IHF was shown to be involved in the regulation of the expression of the type IV pilus that is necessary for the establishment of the colonization of the mucosal surfaces by the meningococcus (18,19). Although it was shown in Escherichia coli that Fur and the regulatory factors H-NS and IHF cooperate to regulate the expression of the gene encoding the iron superoxide dismutase (20), in N. meningitidis the nadA gene is the first indication of a gene that is apparently regulated by both IHF and Fur.…”
Section: Discussionmentioning
confidence: 99%